Electrical properties and thermal degradation of poly(vinyl chloride)/polyvinylidene fluoride/ZnO polymer nanocomposites. Issue 9 (10th June 2016) - Pandey, Mayank; Joshi, Girish M; Mukherjee, Amitava; Thomas, P
Abstract: In this work, polymer nanocomposites consisting of a poly(vinyl chloride) (PVC) and polyvinylidene fluoride (PVDF) polymer network with ZnO nanoparticles as a dopant were prepared by solution casting. An XRD study of the PVC/PVDF/ZnO polymer nanocomposites shows predominantly sharp and high intensity peaks. However, the intensity and sharpness of the XRD peaks decreases with further increment in loading of ZnO (wt%), which reveals a proper intercalation of ZnO nanoparticles within the PVC/PVDF polymer system. Fourier transform infrared spectroscopy has been used to verify the chemical compositional change as a function of ZnO nanoparticle loading. TGA analysis clearly describes the thermal degradation of the pure polymer and polymer nanocomposites. The complex dielectric function, AC electrical conductivity and impedance spectra of these nanocomposites were investigated over the frequency range from 10 Hz to 35 MHz. These spectra were studied with respect to the Wagner − Maxwell − Sillars phenomenon in the low frequency region. Nyquist plots of the PVC/PVDF/ZnO nanocomposites were established from impedance measurements. The temperature‐dependent DC ionic conductivity obtained from the Nyquist plots follows Arrhenius behaviour. © 2016 Society of Chemical Industry Abstract : The incorporation of ZnO nanoparticles in a polyvinylidene fluoride (PVDF) and poly(vinyl chloride) (PVC) homogeneous blend follows Maxwell − Sillars theory and is explained by dielectric studies.